2018
DOI: 10.1007/s10111-017-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying rail asset maintenance processes: a human-centric and sensemaking approach

Abstract: Efficient asset maintenance is key for delivering services such as transport. Current rail maintenance processes have been mostly reactive with a recent shift towards exploring proactive modes. The introduction of new ubiquitous technologies and advanced data analytics facilitates the embedding of a 'predict-and-prevent' approach to managing assets. Successful, user-centred integration of such technology is still, however, a sparsely understood area. This study reports results from a set of interviews, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These findings on fishermen's sensemaking are very similar to sensemaking behaviors found in other domains (Baber and McMaster, 2016;Klein et al, 2007;Weick, 1995). During their routine on fish capture expeditions, fishermen continuously monitor if something goes wrong, exchanging different modes of sensemaking (Kefalidou et al, 2018): individual, based on their own assessments and needs; collaborative, based on information coming from other fishermen; and artefact-based, weather bulletins, Lightning, GPS, and Cellphones. It was found that these different sensemaking modes emerge and are combined within the variability of routine (normal) expeditions, when fishermen make sense of an incident situation.…”
Section: Actions Descriptionmentioning
confidence: 99%
“…These findings on fishermen's sensemaking are very similar to sensemaking behaviors found in other domains (Baber and McMaster, 2016;Klein et al, 2007;Weick, 1995). During their routine on fish capture expeditions, fishermen continuously monitor if something goes wrong, exchanging different modes of sensemaking (Kefalidou et al, 2018): individual, based on their own assessments and needs; collaborative, based on information coming from other fishermen; and artefact-based, weather bulletins, Lightning, GPS, and Cellphones. It was found that these different sensemaking modes emerge and are combined within the variability of routine (normal) expeditions, when fishermen make sense of an incident situation.…”
Section: Actions Descriptionmentioning
confidence: 99%
“…Finally, the root cause of failure in some selected subsystems and components of the railway infrastructure assets [14]. The use of reliability-centered maintenance, predictive maintenance programs, and expert-based rail data for the assessment of the root cause of failure, fault detection, and failure diagnosis in railway infrastructure assets is an interesting topic in reliability management studies [15]. Railway infrastructure in general can be classified into the following two assets [16]:…”
Section: Introductionmentioning
confidence: 99%
“…Recent traffic management applications with different objectives or priorities have been reviewed by Corman et al 1,2 TM problems are usually formulated by different mathematical models and solved with various advanced algorithms. Past research includes various TMS for freight rail, 3 passenger rail, [4][5][6] urban rail transit system 7,8 whose objectives are mainly improving the efficiency of multiple aspects of railway operations directly associated with the TMS, and intelligent maintenance system covering the maintenance of railway track, 9 railway asset, 10 entire railway infrastructure, 11 etc., which also minimise the cost of operating the railway and ensure stable daily services.…”
Section: Introductionmentioning
confidence: 99%